(untitled) (Marketing Journal, 2026)
This article examines the theoretical foundations of Lean Manufacturing and its impact on the economic efficiency of industrial enterprises based on a systematic literature review . The study draws upon the principles of the Toyota Production System and the five core Lean principles developed by Womack and Jones . It analyzes the mechanisms through which tools such as 5S, Kaizen , JIT, VSM, TPM, and Kanban № 1 -SON YANVA R, 202 6-YIL 573 influence production performance . The findings indicate that Lean implementation enhances labor productivity , reduces inventory levels , and minimizes operational waste , thereby strengthening enterprise competitiveness . The paper also provides practical recommendations for the phased implementation of Lean systems in developing economies .